Some Common Diseases of Pepper in Florida - Gary Vallad; Pamela Roberts (EDIS)
This is a minor revision of Circular 946, which was originally published March 1991, by Ken Pernezny and Tom Kucharek and revised September 2015 by Gary Vallad and Pamela Roberts.